REVEALING A JAVANESE IDENTITY OF PRAYER IN THE WEDHATAMA THROUGH SEMANTIC PROPOSITION - Indhiarti, Tantri Refa; Budi, Sri Utami; Winarni, Indah (Kajian Linguistik dan Sastra, 2017)
TheÂ  Wedhatama,Â  aÂ  JavaneseÂ  literaryÂ  workÂ  byÂ  theÂ  KingÂ  MangkunegaraÂ IVÂ  containsÂ  philosophicalÂ  teachingsÂ  whichÂ  areÂ  quiteÂ  influentialÂ  inÂ  ethical life.Â  ThisÂ  paperÂ  aimsÂ  at discovering the hidden meaning of the teachings which revealÂ  anÂ  esotericÂ  knowledgeÂ  ofÂ  worshippingÂ  inÂ  termsÂ  ofÂ  itsÂ  semanticÂ  pointÂ  of view.Â  ThisÂ  meaningÂ  isÂ  knownÂ  throughÂ  analyticÂ  andÂ  syntheticÂ  propositionsÂ  in Gambuh canto associated with 4 different types of worship. Thus, the qualitative paradigm is used in which the data were obtained through library research. In thisÂ  study,Â  theÂ  syntheticÂ  propositionÂ  shows theÂ  breadthÂ  ofÂ  theÂ  poetâsÂ  signifying esoteric intentionÂ  thatÂ  is about Javanese identity ofÂ  prayer. ItÂ  isÂ  revealedÂ  that theÂ  fourÂ  typesÂ  ofÂ  worshipÂ  âsembahÂ  raga,Â  cipta,Â  jiwa,Â  andÂ  rasaÂ  âareÂ  saidÂ  to coincide with what are usually referred to in Muslim Sufism as syariat.Â Keywords: Gambuh canto, the Wedhatama, Javanese identity of prayer, semantic propositionÂ